Infant sex differences in human milk intake and composition from 1- to 3-month post-delivery in a healthy United States cohort - Erin K. Eckart; Jennifer D. Peck; Elyse O. Kharbanda; Emily M. Nagel; David A. Fields; Ellen W. Demerath (Taylor & Francis Group, 2021)
Background Macronutrient composition of human milk differs by infant sex, but few studies have examined sex differences in other milk components, or their potential modification by maternal body mass index (BMI). Aim We compared milk intake and human milk hormone and cytokine concentrations at 1- and 3-month post-delivery and tested infant sex by maternal BMI (OW/OB vs. NW) interactions. Subjects and method Data were analysed for 346 mother-infant dyads in the Mothers and Infants Linked for Healthy Growth (MILk) Study at 1- and 3-month post-delivery. Infant milk intake was estimated by the change in infant weight after test feedings. Concentrations of glucose, insulin, leptin, adiponectin, interleukin-6 (IL-6), and C-reactive protein (CRP) were measured using ELISA. Multivariable linear regression and linear mixed models were used to estimate sex main effects and their interaction with maternal BMI. Results Mean glucose concentration at 1 month was 2.62 mg/dl higher for male infants, but no difference at 3 months was observed. Milk intake and concentrations for the other milk components were similar for males and females at both time points. Associations with infant sex did not differ significantly by maternal BMI. Conclusions Among healthy United States mother-infant dyads, appetite, and growth-regulating factors in human milk did not differ significantly by infant sex.